Evaluation of the influence of wind-driven rain on moisture in cellular concrete wall boards - Alsabry, Abdrahman; Nikitsin, Vadim I.; Kofanov, Vladimir Aleksandrovič; Backiel-Brzozowska, Beata (Zielona Góra: Uniwersytet Zielonogórski)
The non-stationary moisture level of a cellular concrete wall board in a heated utility building located in the northern part of the town of Brest (Belarus), depending on the climatic influence, was assessed in this work. The results were obtained both in a calculation experiment and a physical test. It was observed that the main reason for the high moisture levels in cellular concrete is wind-driven rain intensifying the process of free capillary moisture transfer.
Keywords: cellular concrete; wind-driven rain; capillary transfer; water sorption coefficient; moisture content